If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (6 + 2x) + 14 = 36 Remove parenthesis around (6 + 2x) 2x + 6 + 2x + 14 = 36 Reorder the terms: 6 + 14 + 2x + 2x = 36 Combine like terms: 6 + 14 = 20 20 + 2x + 2x = 36 Combine like terms: 2x + 2x = 4x 20 + 4x = 36 Solving 20 + 4x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 4x = 36 + -20 Combine like terms: 20 + -20 = 0 0 + 4x = 36 + -20 4x = 36 + -20 Combine like terms: 36 + -20 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 15+5*(5+3x)=70 | | 10=-x^2+7x | | 8x-(5x+9)+16=-2 | | 4x+(4x+3)+7=34 | | x-2/3+2/3=6+2/3 | | 3(6-n)=4 | | 2x+5=79-10x | | n-9=27 | | 2y+25=10 | | y-1/4=7/4 | | 4v^2-25= | | -3x-12=-45 | | y-5+5=12+5 | | z-15=32 | | 12k/4k | | x-6+6=14+6 | | 3=-2x-5 | | y+2/75=7.5 | | t-5=-20 | | z+5.5=14 | | (v-8)(v-3)=0 | | n+2.4=5.7 | | 2446566+929299856= | | 6s-10=2+3(-4)+(-4) | | x+3.2=6.8 | | r+15/8=57/8 | | (4x-9)(x-10)= | | 30+7x=4-x | | 10-5=8x+3 | | r+(1)5/8=(5)7/8 | | y+3/4=5/4 | | 3(-7)-9= |